Analytical high frequency channel thermal noise modeling in deep sub-micron MOSFETs - Ong, Shih Ni (2010)
A simple high frequency channel thermal noise model was developed for MOSFETs in strong inversion region. Short channel effects such as channel length modulation effect and mobility degradation due to vertical field were taken into account in the current-voltage model and channel thermal noise model. It was found that the long channel Tsividis’ noise model is still valid for short channel devices by including the proposed effective mobility model and the channel length modulation effect. Good agreement has been obtained between the simulated and measured results across different frequencies, gate biases and drain biases.